Sustainable plastic bottle recycling: employing zinc-deposited SBA-15 as a catalyst for glycolysis of polyethylene terephthalate - Pailin Srisuratsiri; Ketsarin Chantarasunthon; Wanutsanun Sudsai; Pichet Sukprasert; Laksamee Chaicharoenwimolkul Chuaitammakit; Wissawat Sakulsaknimitr (AIMS Environmental Science, 2024)
Novel catalysts for recycling PET bottles into monomers have been developed by depositing zinc onto the surface of SBA-15, mitigating ZnO catalyst agglomeration in glycolysis separation processes to enhance reaction yields. Various zinc compounds (Zn(OAc)2, ZnCl2, and ZnSO4) were employed as substrates for catalyst design on the porous, high-surface-area material SBA-15 via impregnation. The presence of distinct Zn species on SBA-15 was confirmed through XRD and EDS analyses. The acidity of the catalyst, a crucial factor in the PET glycolysis process, was assessed using different Zn-containing precursors. NH3-TPD measurement has revealed the highest acidity in ZnCl2, followed by Zn(OAc)2 and ZnSO4, respectively. Glycolysis reactions with a PET:EG ratio of 1:5 and a 1% catalyst at 200℃ for 2 hours revealed the catalytic efficacy of zinc-deposited compounds in the sequence ZnCl2 > Zn(OAc)2 > ZnSO4. Surprisingly, the ZnCl2 catalyst produced the highest yield of bis-2-hydroxyethyl terephthalate (BHET) at 75% and displayed exceptional recycling capability over three cycles, contributing significantly to resource recovery objectives aligned with the Sustainable Development Goals (SDGs).